A guide to psychotherapy with gay and lesbian clients - Gonsiorek, John C. (New York : Harrington Park Press, 1985)
Fonds Suzan Daniel (FSD)ook uitgegeven als Journal of Homosexuality 07(1981-1982) 2-3
Engels
Monografie